PVDF/MOFs mixed matrix ultrafiltration membrane for efficient water treatment - Cheng, Lilantian; Zhou, Zixun; Li, Lei; Xiao, Pei; Ma, Yun; Liu, Fei; Li, Jian (Frontiers in Chemistry, 2022)
Polyvinylidene fluoride (PVDF), with excellent mechanical strength, thermal stability and chemical corrosion resistance, has become an excellent material for separation membranes fabrication. However, the high hydrophobicity of PVDF membrane surface normally leads a decreased water permeability and serious membrane pollution, which ultimately result in low operational efficiency, short lifespan of membrane, high operation cost and other problems. Metal-organic frameworks (MOFs), have been widely applied for membrane modification due to its large specific surface area, large porosity and adjustable pore size. Currently, numerous MOFs have been synthesised and used to adjust the membrane separation properties. In this study, MIL-53(Al) were blended with PVDF casting solution to prepare ultrafiltration (UF) membrane through a phase separation technique. The optimal separation performance was achieved by varying the concentration of MIL-53(Al). The surface properties and microstructures of the as-prepared membranes with different MIL-53(Al) loading revealed that the incorporation of MIL-53(Al) enhanced the membrane hydrophilicity and increased the porosity and average pore size of the membrane. The optimal membrane decorated with 5 wt% MIL-53(Al) possessed a pure water permeability up to 43.60 L m-2 h−1 bar−1, while maintaining higher rejections towards BSA (82.09%). Meanwhile, the prepared MIL-53(Al)/LiCl@PVDF membranes exhibited an excellent antifouling performance.